Bridging Language Gaps: Internationalizing Local Industry through Bilingual Booklet - Ningsih, Wirda; Gustiani, Sri; Ridhwan, Moehamad; Ma’ruf, Zidni (Dialectical Literature and Educational Journal, 2023)
Abstract: One of the factors that can influence the economic development of a country is the presence of micro, small and medium enterprises (MSME). With the development of technology and globalization of the world, to introduce MSME, it is necessary to create a relevant promotional media. Bilingual booklet is an option that business owner can use to promote their products. This study uses research and design method. English is a widely spoken and understood language in the business world. Creating booklets in English helps companies effectively communicate with a global audience, potential clients, partners, and customers. The aim of the research is to produce a local industry promotion media in the form of a booklet using two languages, English and Indonesian so that it can reach the international market. The stages in designing the booklet itself use the ADDIE model including analyze, design, develop, implement, and evaluate stages. The research location was a local industry in Palembang Pempek Crispy Neny and data was collected through interviews, questionnaires, observation, and documentation. The result of the research is on the formation and development of promotional media for Pempek Crispy Neny bilingual booklet containing information about the products offered by this industry.